Clinical Nutrition Care In Supporting The Patient Healing Process - Masdarwati Masdarwati; Dwi Ardyna Octa Sari; Vivi Adriana Suardi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Clinical nutrition care is an integral part of healthcare services that plays a crucial role in supporting the patient's healing process. Disease conditions, metabolic stress, and inadequate nutritional intake can slow recovery and increase the risk of complications. This study aims to examine the role of clinical nutrition care in supporting the healing process of patients in healthcare facilities. The study used a descriptive-analytical study design with an observational approach. The study sample consisted of 80 inpatients receiving clinical nutrition care. Data were collected through medical record reviews, nutritional status observations, and monitoring of patient clinical outcomes. Data analysis was conducted using descriptive and simple analytical methods. The results showed that patients receiving standardized clinical nutrition care experienced improved nutritional status, increased endurance, and accelerated healing. It was concluded that clinical nutrition care plays a significant role in supporting the success of medical therapy and patient recovery.